(untitled) (Research, Society and Development, 2022)
It is characterized as an impacted tooth, teeth that did not erupt at the physiological time of eruption. These teeth can be impacted in hard tissue, intraosseous, or soft tissue, subgingival. Although it can remain included for a long time and even for the patient’s entire life, many dentists when diagnosing the presence of the impacted tooth choose to remove them. Dental surgeries are most often successful, however, there are factors that can interfere and cause accidents or complications. Therefore, the objective of this study is to identify in the literature the most common accidents and complications in the removal of included teeth, list them as possible causes of accidents and complications and present an adequate protocol for the treatment in case of accidents and complications in the removal of included teeth.